Prevalence of Achromobacter xylosoxidans in pulmonary mucosa‐associated lymphoid tissue lymphoma in different regions of Europe. (23rd December 2013) - Adam, Patrick; Czapiewski, Piotr; Colak, Seba; Kosmidis, Perikles; Tousseyn, Thomas; Sagaert, Xavier; Boudova, Ludmila; Okoń, Krzysztof; Morresi‐Hauf, Alicia; Agostinelli, Claudio; Pileri, Stefano; Pruneri, Giancarlo; et al.
Summary Extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue (MALT lymphoma) comprises 7–8% of B‐cell lymphomas and commonly originates from a background of long‐standing chronic inflammation. An association with distinct bacteria species has been confirmed for several anatomical sites of MALT lymphoma. For pulmonary MALT lymphoma, however, a clear link with an infectious agent or autoimmune disorder has not yet been reported. Using a 16S rRNA gene–based approach, we have recently identified Achromobacter (Alcaligenes) xylosoxidans in eight of nine cases of pulmonary MALT lymphoma. A. xylosoxidans is a gram‐negative betaproteobacterium with low virulence, but high resistance to antibiotic treatment. To further examine a potential association with A. xylosoxidans, 124 cases of pulmonary MALT lymphoma and 82 control tissues from six European countries were analysed using a specific nested PCR. Although prevalence rates for A. xylosoxidans varied significantly from country to country, they were consistently higher for MALT lymphoma as compared to controls. Overall, 57/124 (46%) pulmonary MALT lymphomas and 15/82 (18%) control tissues were positive for A. xylosoxidans (P = 0·004). Whether the significant association of A. xylosoxidans with pulmonary MALT lymphoma demonstrated in our study points to a potential causal role in the pathogenesis of this lymphoma will require further studies.